Erratum: Sumin A.N., Vakhrushev A.K., Shcheglova A.V. Clinical symptoms and ECG data in women with acute coronary syndrome. Acta biomedica scientifica. 2023; 8(3): 70-80. doi: 10.29413/ABS.2023-8.3.7 - Article Editorial (Acta Biomedica Scientifica)
.